Screening and prevalence of vitamin B12 deficiency among pregnant women - Pandey, Mily; Singh, Sarita; Attri, Manish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Vitamin B12 deficiency (serum vitamin B12 <148pmol/L) is considered to be an important cause of anaemia in pregnancy. Pregnant women with this deficiency have an increased risk of developing preeclampsia, intra-uterine growth retardation and preterm labour. The current study was undertaken to determine the prevalence of vitamin B12 deficiency in pregnant women and its association with their dietary habits and socioeconomic status. Methods: This was a cross sectional study conducted in a tertiary care institute over a period of 2 months. Pregnant women visiting antenatal OPD were included in the study and those receiving vitamin B12 supplements, antacids, antiepileptic medication or methotrexate were excluded. Each participant was subjected to a predesigned structured questionnaire and their serum vitamin B12 concentration was done using quantitative determination by microplate enzyme immunoassay. Results: Of the 97 women included, majority were in the age group 20-25years (57.73%). 87.62% (85 women) were found to have anaemia and a total of 44women (45.36%) had vitamin B12 deficiency. Conclusions: The prevalence of vitamin B12 deficiency in north India is considerably high, which may be the cause of neural tube defects and poor birth outcomes and neurological deficit in children born to these mothers.